4. TANGENTS AND NORMALS §4.1 Equation of the Tangent at a Point Recall that the slope of a curve at a point is the slope of the tangent at that point. The slope of the tangent is the value of the derivative at that point. In computing the equation of the tangent we have the slope plus one point, so we use the Slope Plus One Point Equation: y y0 = m(x x0) . Example 1: Find the equation of the tangent to y = 3x2 4x + 7 at x = 1. Solution: When x = 1, y = 6 so the tangent passes through (1, 6). dy dx = 6x 4. When x = 1 the slope is therefore 2. The equation of the tangent is therefore y 6 = 2(x 1) = 2x 2, which simplifies to y = 2x + 4. One common error is to forget to substitute the particular value of x into the derivative. If we’d made that mistake in the above example we’d have concluded that the equation of the tangent is y 6 = (6x 4)(x 1) = 6x2 10x + 4, which simplifies to y = 6x2 10x + 10. But this isn’t even the equation of a straight line. Always make sure that the “m” in the equation is a constant – you must substitute for x in the derivative. TANGENT AT A POINT Find the equation of the tangent to y = f(x) at P(x0, y0). P(x0, y0) (P lies on the curve.) dy (differentiate) dx = Slope of tangent is m = (substitute x = x0). It passes through (x0, y0) so equation of the tangent is: y y0 = m(x x0) i.e. y = (x ) 53 §4.2 Equation of the Normal at a Point When a ray of light reflects off a curved surface, the angle of reflection is the same as the angle of incidence. A normal to a curve is a line that cuts the curve at right angles. It’s therefore perpendicular to the tangent. So we use the same y y0 = m(x x0) equation, but when we substitute into the derivative to get the slope of the tangent we have to invert and change the sign to get the perpendicular slope before substituting for “m”. Example 2: Find the equation of the normal to the curve y = x2 at x = 2. Solution: When x = 2, y = 4 so the normal passes through (2, 4). dy dx = 2x. So the slope of the tangent at x = 2 is 4. The slope of the normal is therefore ¼. The equation of the tangent is therefore y 4 = ( ¼)(x 2) = ¼x + ½ . This simplifies to x + 4y = 18. NORMAL AT A POINT Find the equation of the normal to y = f(x) at P(x0, y0). P(x0, y0) (P lies on the curve.) dy (differentiate) dx = Slope of tangent is (substitute x = x0) 1 Therefore slope of the normal is: = It passes through (x0, y0) so equation y y0 = m(x x0) i.e. y = of the normal is: (x ) §4.3 Equation of Tangent(s) From a Point Suppose we want the tangent or tangents that pass through some point P that doesn’t lie on the curve. Because we don’t know the point of contact we have to work indirectly. Suppose the point of contact is Q, when x = t. The variable “t” is called a “parameter”. It represents one or Q more specific values which we determine later. We now work out the equation of the tangent in terms of “t”. 54 Q P there may several possible Q’s Now the fact that the tangent passes through the given point P means that we can substitute the coordinates of P into this equation. This will give an equation in the parameter “t” which we proceed to solve. Finally we feed each of these values of “t” into the equation of the tangent and so get the final answer. (If this equation has no solutions this simply means there are no tangents passing through the given point.) Example 3: Find the equation of the tangents to y = x2 + x that pass through (1, 1). Solution: Let the point of contact be when x = t. The corresponding y-value is y = t2 + t. So the tangent passes through (t, t2 + t). dy dx = 2x + 1. The slope of he tangent at x = t is 2t + 1. The equation of this tangent is therefore: y (t2 + t) = (2t + 1)(x t). But since the tangent has to pass through (1, 1) we must have 1 (t2 + t) = (2t + 1)(1 t). Simplifying this we get t2 2t = 0 and solving, we get t = 0 or t = 2. When t = 0 the equation of the tangent is y 0 = 1(x 0), that is, y = x. When t = 2 the equation of the tangent is y (4 + 2) = 5(x 2), that is, y = 5x 4. TANGENT FROM A POINT Find the equation of the tangents to y = f(x) which pass through (x0, y0). P(x0, y0) (P does not lie on the curve.) dy (differentiate). dx = Slope of tangent is m = (substitute x = t) Passes through (x0, y0) so equation of tangent is: y f(t) = m(x t) i.e. y = (x t) substitute x = t in original equation BUT it passes through (x0, y0) so = (put x = x0, y = y0 in equation of the tangent to get, after rearrangement = 0 (an equation in t) SOLVE this equation. SUBSTITUTE each solution into to get the required tangents. EXERCISES FOR CHAPTER 4 Exercise 1: The slope of the tangent to a curve at P(2, 5) is 3. Write down the equation of the tangent and the normal at P. 55 Exercise 2: Find the equations of the tangents to the following curves at x = 4. 8 (i) y = x2 3x + 2; (ii) y = x ; 1 (iii) y = x ; (iv) y = ; x3 (v) y = x x + 5 . Exercise 3: Find the normals to the following curves at x = 2: 1 (i) y = 4 x4 + 1; (ii) y = x + 2 ; (iii) y = x x 1 . Exercise 4: Find the tangents to y = x2 5x + 7 that pass through (2, 1). 1 Exercise 5: Find the tangents to y = x that pass through (2, 4). Exercise 6: Find the tangents to y = x that pass through (1, 1). [HINT: You will end up with an equation involving t . To solve this simply put T = t and this will give you a quadratic in T. Once you have solved this for T, take square roots to get the corresponding values for t. Only use positive square roots because t doesn’t exist for negative t.] Exercise 7: If y = 2x3 15x2 + 23x 10 find: dy (a) dx ; (b) the points on this curve where the slope is 1; (c) the tangents at these two points; (d) (harder) the distance between these two parallel tangents. Exercise 8: Find the equations of the three normals to y = x2 that pass through (0, 3/2). [HINT: Proceed as for tangents passing through a point but use the slope of the normal instead of the tangent.] Exercise 9: A train moves along a track in the shape of the parabola y = x2 (distances in kilometres). A road runs along the x-axis and there’s a station at the point where the track and the road come together. You’re in a house 1 km from the station along this road and, as the train approaches the station, the light on the front of the train shines directly in the front window. How many metres away is the train when this occurs (to the nearest 100 metres)? HINT: Let the train be at the point (t, t2). Work out the equation of the tangent at this point. 56 train road station house Exercise 10: A very symmetrical man-made mound rises from an otherwise flat plain. The vertical cross- light pole sections of a hill through the highest point all have the equation y = 9 x2 (with x giving the horizontal distance in metres from the axis of symmetry and y, also in metres, giving the height above the surrounding plain). The horizontal cross-sections are all circular. The mound casts a shadow around the base of the plain. How far from the base of the mound does this shadow reach? mound shadow SOLUTIONS FOR CHAPTER 4 Exercise 1: The equation of the tangent is y – y1 = m (x – x1), where m is the slope of the tangent and (x0, y0) is the point on the curve. So in this case we have: y – 5 = 3 (x – 2) which can be simplified to 3x – y – 5 = 0. 1 1 The slope of the normal is – 3 so the equation of the normal is y – 5 = 3 (x 2) which can be simplified to x + 3y = 17. Exercise 2: dy dy (i) dx = 2x 3. When x = 4, y = 6 and dx = 5. The equation of the tangent is thus: y 6 = 5(x 4) which can be simplified to 5x y = 14. dy 8 dy 1 (ii) dx = x2 . When x = 4, y = 2 and dx = 2 . The equation of the tangent is thus: 1 y 2 = 2 (x 4) which can be simplified to x + 2y = 8. dy 1 dy 1 (iii) dx = . When x = 4, y = 2 and dx = 4 . The equation of the tangent is thus: 2 x 1 y 2 = 4 (x 4) which can be simplified to x 4y + 4 = 0. dy 1 dy 1 (iv) dx = 2 (x 3)3/2. When x = 4, y = 1 and dx = 2 . The equation of the tangent is thus: 1 y 1 = 2 (x 4) which can be simplified to x + 2y = 6. Exercise 3: dy dy 1 (i) dx = x3. When x = 2, y = 5 and dx = 8. The slope of the normal is thus 8 and so the 1 equation of the normal is y 5 = 8 (x 2) which can be simplified to x + 8y = 42. dy 1 dy 1 (ii) dx = . When x = 2, y = 2 and dx = 4 . The slope of the normal is thus 4 and so 2 x+2 the equation of the normal is y 2 = 4(x 2) which can be simplified to x + y = 10. 57 dy 1 x + 2(x 1) 3x 2 dy =x. + 1. x 1 = = . When x = 2, y = 2 and = 2. dx dx 2 x1 2 x1 2 x1 1 1 The slope of the normal is thus 2 and so the equation of the normal is y 2 = 2 (x 2) which can be simplified to x + 2y = 6. (iii) Exercise 4: Let the point of contact of the tangent be Q(t, t2 5t + 7). dy dx = 2x 5 so the slope of the tangent at Q is 2t 5. The equation of the tangent at Q is thus y (t2 5t + 7) = (2t 5)(x t). Since this tangent passes through (2, 1) we have: 1 (t2 5t + 7) = (2t 5)(2 t) which can be simplified to t2 4t + 4 = 0. This gives (t 2)2 = 0 so t = 2 is the only solution. There is therefore only one tangent through (2, 1). Substituting t = 2 into the equation of the tangent we get y 1 = (x 2) which can be simplified to x + y = 3. Exercise 5: 1 Let the point of contact of the tangent be Q(t, t ). dy 1 1 dx = t2 so the slope of the tangent at Q is t2 . 1 1 The equation of the tangent at Q is thus y t = t2 (x t). Since this tangent passes through (2, 4) we have: 1 1 4 t = t2 (2 t) which can be simplified to 4t2 + 2t 2 = 0. Dividing by 2 gives 2t2 + t 1 = (2t 1)(t + 1) = 0. This has two solutions: t = ½ and t = 1. 1 Substituting t = 2 into the equation of the tangent we get y 2 = 4(x ½) which can be simplified to 4x + y = 4. Exercise 6: Let the point of contact of the tangent be Q(t, t ). dy 1 1 dx = 2 t so the slope of the tangent at Q is 2 t . The equation of the tangent at Q is thus y t = 1 2 t (x t). Since this tangent passes through (1, 1) we have: 1 1 t = (1 t) which can be simplified to 3t 2 t 1 = 0. 2 t Substituting T = t gives us 3T2 2T 1 = (3T + 1)(T 1) = 0. 1 This has two solutions: T = 1 and T = 3 . But since T = t can’t be negative, T = 1 is the only solution. It corresponds to t = 1. 58 Substituting t = 1 into the equation of the tangent we get y 1 = 1 (x 1) which can be 2 simplified to x + 2y = 3. Exercise 7: dy (a) dx = 6x2 – 30x + 23 dy (b) If dx = –1 then 6x2 30 x + 24 = 0. Dividing by 6 gives x2 5x + 4 = (x 1)(x 4) = 0 so x = 1 or 4. When x = 1, y = 0 and when x = 4, y = 30. So the required points are (1, 0) and (4, 30). (c) The tangent at (1, 0) is x + y –1 = 0 and the tangent at (4, 30) is x + y + 26 = 0. (d) 1 x + y –1 = 0 26 x + y + 26 = 0 Consider the dotted line passing through (0,1) that cuts both lines at right angles. Now the shaded right- angled triangle has a hypotenuse with the other two sides equal. Suppose the lengths of these other two sides is x. Using Pythagoras theorem we have x2 + x2 = 25 which 25 5 2 5 gives x = = = . This is the distance between these two parallel tangents. 2 2 2 Exercise 8: Let the normal be at the point Q(t, t2). dy 1 = 2t so the slope of the normal at Q is dx 2t . 1 The equation of the normal at Q is thus y t2 = 2t (x t). Since this normal passes through (0, 3/2) we have: 1 3/2 t2 = 2t (0 t) which can be simplified to 2t3 = 2t. This has solutions t = 0 and 1. (Don’t forget the t = 0 possibility. If you divided by t you were ignoring this case.) So there are three normals that pass though (0, 3/2). The normal for t = 0 is the y-axis, x = 0. For t = 1 the normal is y 1 = ½ (x 1) which can be simplified to x + 2y = 3. For t = 1 the normal is y 1 = ½ (x + 1) which can be simplified to x 2y = 3. Exercise 9: The house is at the point (1, 0) so we want to find the tangents that pass through this point. 59 Let the point of contact of the tangent (the position of the train) be T(t, t2). dy dx = 2x so the slope of the tangent at T is 2t. The equation of the tangent at T is thus y t2 = 2t (x t). Since this tangent passes through (1, 0) we have: 0 t2 = 2t (1 t) which can be simplified to t2 2t = 0. The solutions for t are t = 0 or 2. If t = 0 the train is at (0, 0), the station. Although the tangent at this point passes through (1, 0) when the train is at the station the light might come through the side window of the house, but not the front window. So we reject this case. This leaves t = 2, which puts the train at (2, 4). The distance between the house at H(1, 0) and the train at T(2, 4) is (2 1)2 + (4 0)2 = 17 4.123105626. Because of the scale this represents 4.123105626 kilometres. Now it would be ridiculous to give the answer to such a question to this degree of accuracy. After all the train and the house are rather large objects. Probably an answer to the nearest 10 metres is appropriate. So we give our answer as 4120 metres. Question 10: The cross-section of the mound is described by the equation y = 9 x2 where the origin is at the centre of the base of the mound. Distances are in metres. The curve y = 9 x2 cuts the x-axis at x = 3 so the base of the mound is a circle with radius 3. The top of the mound is at (0, 9) and the light is at (0, 12). The furthest points of the shadow are where the tangent at some point cut the x-axis. We don’t know where this point is, but we do know that the tangent passes through (0, 12). So we want to find the equations of the tangents that pass through (0,12). Let the point of contact of the tangent be T(t, 9 t2). dy dx = 2x so the slope of the tangent at T is 2t. The equation of the tangent at T is thus y (9 t2) = 2t (x t). Since this tangent passes through (0, 12) we have: 12 (9 t2) = 2t (0 t) which can be simplified to t2 = 3. The solutions for t are t = 3 . If t = 3 the equation of the tangent is y (9 3) = 2 3 (x 3 ) which can be simplified to 2 3 x + y = 12. 12 This cuts the x-axis (y = 0) at x = . Multiplying top and bottom by 3 gives 2 3 x = 2 3 3.464101615. This represents a distance of 3.46 metres from the centre of the base of the mound (any greater accuracy wouldn’t be appropriate). But the mound has a radius of 3 metres so the furthest the shadow reaches from the base of the mound is 0.46 metres, which is better expressed as 46 centimetres. 60